PENGARUH MEDIA PEMBELAJARAN INTERAKTIF PIVOT OFF LINE TERHADAP MINAT BELAJAR SISWA DI SMA NEGERI 1 PINANGSORI - Ainun Mardiyah Lubis (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
This research is a quasi-experimental study aimed to determine the effect of Pivot off line interactive learning media on students' interest in learning physics at Pinangsori 1 High School and to know the effect of Pivot off line interactive learning media on student physics learning outcomes on business (work) and kinetic energy material in Pinangsori 1 High School. The population in this study were all students of class X MIA SMA Negeri 1 Pinangsori, which consisted of 4 classes (130 students). The sample of this study was determined by random cluster sampling, amounting to 30 people. The research instrument is learning interest. The average value of the final ability (Post-test) in the experimental class after the implementation of learning methods assisted by Pivot Animator software increased. The experimental class post-test results are (for max = 95, min = 75, dan = 84,3), while the control class post-test results are (for max = 80, min = 60, dan = 73,1). The initial results of the questionnaire students' interest in learning physics in the experimental class were (for max = 90, min = 60, dan = 79,3),, while in the control class were (for max = 80, min = 50, dan = 69,1) it can be concluded that Pivot off line interactive learning media on students' learning interest in Pinangsori 1 High School.